PERLINDUNGAN HUKUM TERHADAP MEREK TERKENAL (WELL-KNOWN) DI INDONESIA: Citra Rosa Budiman - admin, admin (Reformasi Hukum, 2019)
In Indonesia today there is still a violation of the brand in business activities carried out ranging from street vendors to inside the mall. The first problem is how to protect the law for well-known or well-known brands in Indonesia? and second, how is Indonesia's role in upholding intellectual property law in the international world? The purpose of this research is to find out the legal protection arrangements for well-known or well-known brands in Indonesia and to know the legal politics of criminal violation of famous brands in Indonesia. Its usefulness is to provide information on legal protection arrangements for well-known or well-known brands in Indonesia and to know the legal politics of criminal violation of well-known brands in Indonesia. The research method is normative legal research. The results of the study show that in the TRIPs Agreement, infringement of well-known marks is implicitly regulated in the provisions of Article 16 paragraph (3) of the TRIPs Agreement and Article 6 paragraph (2) of Law No. 15 of 2001 concerning Marks which regulate the protection of famous marks on goods and / or services which are not of the same type. The conclusion is that legal protection for well-known or well-known brands in Indonesia has been regulated in Law No. 15 of 2001 concerning Trademarks and Approval of TRIPs and in the enforcement of intellectual property law in the international world Indonesia is a member of the WTO (World Trade Organization) Agreement and has ratified it in Law No. 7 of 1994, which has made Indonesia automatically bound to the TRIPs Agreement.